(untitled) (African Journal of Law and Politics, 2025)
Today, new information and communication technologies constitute a logical engine of change leading to the performance and efficiency of organization. According to the power accelerator that is Covid- 19, we have seen a change in the logical pattern of how businesses operate. In new digital configuration, telematics has become a work tool by excellence. From Facebook to Amazon via Twitter, Instagram, discussion forums, blogs, messaging, etc., a new stakeholder management ecosystem has quickly been established. The Internet revolution impacts not only the organization of work, but also the behavior of employees. The multiplication and variety of possible uses of NICTs, however, requires control of their use by both employers and employees, in order to limit abuses and attacks on fundamental rights and the logic of fair competition.